Analisis Pengukuran Kepuasan Konsumen dengan Pendekatan Customer Satisfaction Indeks Pada E-Commerce di Jakarta - Oki Lestari; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of e-commerce is currently increasingly rapid, marked by the increasing number of internet users in Indonesia. Customer satisfaction and trust are the most dominant problems in every business unit operating in the service sector, but the process of achieving customer satisfaction is not easy. Because many other factors can influence the achievement of this level of customer satisfaction. Through this research, the author aims to determine the level of customer satisfaction, namely by using the Customer Satisfaction Index method. Based on the research results, it is known that female consumers, consumers aged 23-28 years, and private employees are the dominant respondents. The level of consumer satisfaction with e-commerce based on CSI is 97.12%.